The Existence of Opposition to Youth Participation Rate as an Effort to Improve Political Education - Rustandi, Apriya Maharani; Suryadi, Karim (Proceeding International Conference on Religion, Science and Education, 2022)
The existence of the opposition is necessary for a democratic country, which in general is very influential on the quality of democracy. The quality of a good democracy cannot be separated from youth participation and political education. Researchers conducted a literature review to examine the presence of opposition to youth participation in improving political education. Researchers conducted a review of 38 articles from 2015 to 2020, then focused on observing the research progress of political education applied to youth. The results of this review indicate that these variables, the presence of opposition to the level of youth participation, are more suitable to be executed using political education. Overall, this review provides an appropriate reference point for further research by identifying research needs in oppositional aspects, especially in providing existence on the level of youth participation and political education.